A high efficiency and high speed charge of Li-Ion battery charger interface using switching-based technique in 180 nm CMOS technology - Mustapha El Alaoui; Fouad Farah; Karim El khadiri; Ahmed Tahiri; Rachid El Alami; Hassan Qjidaa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In this work, the design and analysis of new Li-Ion battery charger interface using the switching-based technique is proposed for high efficiency, high speed charge and low area. The high efficiency, the lower size area and the fast charge are the more important norms of the proposed Li-Ion battery charger interface. The battery charging is completed passes to each charging mode: The first mode is the trickle charge mode (TC), the second mode is the constant current mode (CC) and the last mode is the constant voltage mode (CV), in thirty three minutes. The new Li-Ion battery charger interface is designed, simulated and layouted in Cadence software using TSCM 180 nm CMOS technology. With an input voltage VIN = 4.5 V, the output battery voltage (VBAT) may range from 2.7 V to 4.2 V and the maximum charging battery current (IBAT) is 1.7 A. The peak efficiency reaches 97% and the total area is only 0.03mm2 .